The Influence of Learning Community, Teacher Work Motivation, and Academic Supervision on the Learning Quality of Elementary Schools in Bergas District - Ahmad Farian Listianto; Nurkolis; Endang Wuryandini (MIMBAR PGSD Undiksha, 2025)
This study aims to examine the influence of learning communities, teacher work motivation, and academic supervision on the quality of learning in elementary schools, both partially and simultaneously. The research employed a quantitative approach with a correlational research design. The study population consisted of 259 elementary school teachers, and a sample of 157 teachers was selected using proportional random sampling. Data were collected through Likert-scale questionnaires and analyzed using descriptive statistics, prerequisite tests (normality, multicollinearity, heteroscedasticity, and linearity), and hypothesis testing through simple and multiple linear regression analyses. The findings show that learning communities significantly influence learning quality with a coefficient of 0.546 and a contribution of 25.2%. Teacher work motivation has a significant influence of 0.776 with a contribution of 56.3%, while academic supervision significantly affects learning quality with a coefficient of 0.658 and a contribution of 40.9%. Simultaneously, the three variables exert a significant influence on learning quality, as reflected in the regression equation Ŷ = −25.594 + 0.250X₁ + 0.574X₂ + 0.412X₃ and a coefficient of determination of 0.844 or 84.4%. The study concludes that learning communities, teacher work motivation, and academic supervision have significant effects on the quality of learning in elementary schools, both individually and collectively. It is recommended that school principals strengthen collaborative cultures through teacher learning communities, enhance work motivation through recognition and supportive work environments, and optimize continuous academic supervision to improve learning quality.